Dialectical Behavior Therapy Technique on the Psychological Well-Being of Adolescents from Broken Home Families - Denofal; Isriyah, Mudafiatun; Maghfiroh, Nasruliyah Hikmatul (International Journal of Research in Education, 2025)
Adolescents from broken home families are vulnerable to psychological well-being disturbances, such as feelings of worthlessness, difficulties in managing emotions, and impaired social relationships. This condition requires appropriate intervention to help individuals achieve emotional balance and improve their social adaptation. This study aims to develop and examine the effectiveness of a Dialectical Behavior Therapy (DBT) module in enhancing the psychological well-being of adolescents from broken home families within the madrasah educational environment. The research approach used was Research and Development (R&D) with the ADDIE model, focusing on the development of an instructional product in the form of a counseling service module. The research subjects consisted of six adolescents who were identified as victims of broken home families based on the results of an initial assessment. The Dialectical Behavior Therapy (DBT) module was developed through the stages of planning, preparation, expert validation, and limited trial. The results of the study show that the implementation of the Dialectical Behavior Therapy (DBT) module significantly improves aspects of self-awareness, emotional regulation, interpersonal relationships, and the ability to cope with stress. In conclusion, the developed Dialectical Behavior Therapy (DBT) module proves to be effective and feasible as an intervention tool to enhance the psychological well-being of adolescents from broken home families. This module is expected to serve as a practical alternative for psychological support within the madrasah educational environment.